2000
DOI: 10.1034/j.1398-9995.2000.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of dust‐mite allergens (Lep d 2, Der p 1, Der f 1, Der 2) in pig‐farming environments and sensitization of the respective farmers

Abstract: Allergen exposure at the workplace is strongly related to the concentration of allergens in farmers' beds. Exposure to domestic mite allergens should be taken into account when assessing occupational exposure to allergens and the respiratory health of farmers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
32
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 33 publications
(27 reference statements)
6
32
1
Order By: Relevance
“…Recent studies have shown a lower prevalence for the development of asthma and allergies among farmers [16,17] and children living on farms [18,19]. Thus, one may speculate that living on farms might have a protective effect for the development of allergies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown a lower prevalence for the development of asthma and allergies among farmers [16,17] and children living on farms [18,19]. Thus, one may speculate that living on farms might have a protective effect for the development of allergies.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitization to storage mites prevails in many studies in which the participants are farmers or mainly farmers [25, 33, 34]. A study from Germany conducted among pig farmers revealed that median concentrations of the D. pteronyssinus-1 allergen were 50-fold higher in farmer’s beds than in the beds of an urban control group, and L. destructor-2 allergen concentrations tended to be higher in farmer’s beds compared to the urban control group [35]. However, comparing the prevalence of allergic sensitization between farmers and the urban population, no difference was found [35].…”
Section: Discussionmentioning
confidence: 99%
“…A study from Germany conducted among pig farmers revealed that median concentrations of the D. pteronyssinus-1 allergen were 50-fold higher in farmer’s beds than in the beds of an urban control group, and L. destructor-2 allergen concentrations tended to be higher in farmer’s beds compared to the urban control group [35]. However, comparing the prevalence of allergic sensitization between farmers and the urban population, no difference was found [35]. In our study, the participation was not preconditioned by any occupational setting like farming.…”
Section: Discussionmentioning
confidence: 99%
“…Animal facilities, including experimental laboratories, zoo cages, and pig and poultry farms studied in Germany, Poland, Finland, and Croatia showed generally low exposure to pyroglyphid mites (40)(41)(42), save for a few poultry farm samples exceeding the sensitisation threshold (43).…”
Section: Exposure To House Dust Mites In Public/occupational Settingsmentioning
confidence: 99%